Parasitic nematodes of the genus Syphacia Seurat, 1916 infecting Cricetidae in the British Isles: the enigmatic status of Syphacia nigeriana. Issue 1 (5th January 2022) - Behnke, Jerzy M.; Stewart, Alex; Smales, Lesley; Cooper, Gemma; Lowe, Ann; Kinsella, John M.; Bajer, Anna; Dwużnik-Szarek, Dorota; Herman, Jeremy; Fenn, Jonathan; Catalano, Stefano; Diagne, Christophe A.; et al.
Abstract: Abstract: Oxyurid nematodes ( Syphacia spp.) from bank ( Myodes glareolus) and field/common ( Microtus spp.) voles, from disparate geographical sites in the British Isles, were examined morphologically and genetically. The genetic signatures of 118 new isolates are provided, based primarily on the rDNA internal transcribed spacers (ITS1-5.8S-ITS2) region and for representative isolates also on the small subunit 18S rDNA region and cytochrome c oxidase subunit 1 ( cox-1 ) gene locus. Genetic data on worms recovered from Microtus spp. from the European mainland and from other rodent genera from the Palaearctic, North America and West Africa are also included. We test historical hypotheses indicating that S. nigeriana is a generalist species, infecting a range of different rodent genera. Our results establish that S. nigeriana is a parasite of both bank and field voles in the British Isles. An identical genotype was also recorded from Hubert's multimammate mouse ( Mastomys huberti ) from Senegal, but Mastomys spp. from West Africa were additionally parasitized by a related, although genetically distinct Syphacia species. We found no evidence for S. petrusewiczi in voles from the British Isles but isolates from Russia and North America were genetically distinct and formed their own separate deep branch in maximum likelihood molecular phylogenetic trees.